Midnight timetable : a novel in ghost stories - 정 보라, 1976- (Algonquin Books of Chapel Hill / Little, Brown and Company, 2025)
"When the Institute's newest employee arrives for their first night shift, they begin to see why some workers don't last long in the job. Things and people seem to change in these dimly lit halls, where those who opent he wrong door might find it's disappeared behind them or that the echoing footsteps they're running from are their own. Not everyone is suited to the work of protecting the Institute's strange artifacts. Equal parts bone-chilling, wryly funny, and deeply political, Midnight Timetable is a masterful work of literary horror from one of our time's greatest imaginations" -- Provided by publisher.